Misandry and Resistance in Sylvia Plath’s Mushrooms and Lady Lazarus - Karo, Hassan; Hassan, Saman (Humanities Journal of University of Zakho, 2020)
This paper discusses the two concepts of misandry and resistance in two famous poems by Sylvia Plath, namely Mushrooms (1959) and Lady Lazarus (1962). It focuses on the sufferings of women in the distressful life conditions they witness in patriarchal societies. It also reveals men’s perception of women in male-dominated communities and the reaction of women to such perceptions. Through the female speakers of the poems, Plath stands against the patriarchal norms. She expresses her resentment at men’s treatment of women. The paper takes into consideration the critical views of three French feminist–psychoanalytic theorists− Julia Kristeva (1941- ), Helene Cixous (1937- ), and Luce Irigaray (1930- )− to provide a concrete poetic analysis of the two selected poems. In this study, Plath is shown to represent the entire post-WWII female generation. The study sheds light on the domestic environment women were living and how they were oppressed in society by men. It aims to illustrate the obstacles that failed women to speak up and discover their own identity. The study argues that the difficult life women experienced has made them develop the sense of misandry and resist the tyrannical rule of men. The paper covers the two poems in a chronological order: first, Mushrooms, which is normally regarded as Plath’s preparation for the fight against patriarchy, and then, Lady Lazarus, which symbolizes resistance and triumph over the oppressive power of men.